A Network Administration on Windows Server 2016 at Aman Sari Village Office - Farida Gultom (PT Inovasi Pratama Internasional, 2021)
In today's era, technological developments are very influential for offices, schools, and companies. Now technology has been widely used especially in the world of communication and information that already uses computer networks to accelerate fast and efficient data transmission. All components incorporated in a computer network must support each other to produce a good and easy system to serve customers. Network is always useful and helps in increasing the effectiveness and efficiency.